Harmoni Antarbudaya dalam Secangkir Teh: Kajian Gong Fu Cha Pantjoran Tea House - Nathania, Angela Cheryl; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Harmony in society is the key to peaceful and positive coexistence. Gong Fu Cha has great potential as a bridge of intercultural communication to support the harmonization of multicultural Indonesian society. The problem examined in this research centers on the practice of Gong Fu Cha as a bridge of Chinese cultural communication carried out by Pantjoran Tea House and as a form of marketing communication that makes its business differentiation. This research uses Intercultural Communication Theory and Marketing Communication Theory to observe the harmony between its participants that strengthens cross-cultural understanding and appreciation. This research employs a qualitative approach with ethnographic methods, utilizing data collection techniques such as participatory observation and in-depth interviews, complemented by literature reviews. Thematic analysis was used to identify patterns of social interaction and data triangulation was utilized to ensure data validity. The outcome of this research is that Gong Fu Cha at Pantjoran Tea House is an effective means of marketing communication in communicating Chinese culture through direct experience, opening space for dialogue, and building harmony between its participants, especially in terms of tolerance between ethnicities. Gong Fu Cha can be a symbol of equality, enabling harmonious interactions for its participants and enhancing appreciation in a multicultural society. Harmoni dalam masyarakat adalah kunci hidup berdampingan secara damai dan positif. Gong Fu Cha memiliki potensi besar sebagai jembatan komunikasi antarbudaya untuk mendukung harmonisasi masyarakat Indonesia yang multikultural. Permasalahan yang ingin dikaji dalam penelitian ini berfokus pada praktik Gong Fu Cha sebagai jembatan komunikasi budaya Tionghoa yang dilakukan Pantjoran Tea House serta sebagai bentuk komunikasi pemasarannya yang menjadikan diferensiasi bisnisnya. Penelitian ini menggunakan Teori Komunikasi Antarbudaya dan Teori Komunikasi Pemasaran dalam mengamati harmoni antar partisipannya yang tercipta serta memperkuat pemahaman dan penghargaan lintas budaya. Penelitian ini menerapkan pendekatan kualitatif dengan metode etnografi, menggunakan teknik pengumpulan data berupa observasi partisipatif dan wawancara mendalam, serta dilengkapi dengan studi literatur. Data dianalisis secara tematik untuk mengidentifikasi pola interaksi sosial dan memastikan validitas data melalui triangulasi data. Hasil dari penelitian ini adalah Gong Fu Cha di Pantjoran Tea House menjadi sarana efektif sebagai komunikasi pemasaran dalam mengkomunikasikan budaya Tionghoa melalui pengalaman langsung, membuka ruang dialog, dan membangun keharmonisan antar partisipannya terutama dalam segi toleransi antar etnis. Gong Fu Cha dapat menjadi simbol kesetaraan, memungkinkan interaksi harmonis bagi partisipannya serta meningkatkan apresiasi dalam hidup bermasyarakat yang multikultural.